2021
DOI: 10.3390/nu13051452
|View full text |Cite
|
Sign up to set email alerts
|

Measuring and Leveraging Motives and Values in Dietary Interventions

Abstract: Why measure and leverage food motives and values? Every failure and every success in dietary change can be connected to motivation. Therefore, this research question naturally arises: How can food motives and values be measured and leveraged to improve diet outcomes from the individual to populations? There are four ways that food motives and values (FMVs) can assist researchers and health professionals. First, FMVs can help to create a personalized approach to dietary change. Second, FMVs can inform content f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…We feel it's a missed opportunity for Tricò et al to not report on the satisfaction participants have with study diets or on other potentially relevant individual-level factors (e.g., cost, familiarity). The practical implications for motivating food factors and values within interventions has been recently examined by Eustis and colleagues [7]. In our own trials, we have found varying psychosocial, demographic, and environmental motivational factors regarding adherence to study diets [6,8,9].…”
mentioning
confidence: 58%
“…We feel it's a missed opportunity for Tricò et al to not report on the satisfaction participants have with study diets or on other potentially relevant individual-level factors (e.g., cost, familiarity). The practical implications for motivating food factors and values within interventions has been recently examined by Eustis and colleagues [7]. In our own trials, we have found varying psychosocial, demographic, and environmental motivational factors regarding adherence to study diets [6,8,9].…”
mentioning
confidence: 58%
“…These inspiration sources and motives can inform content for dietary interventions. Best-practice public health nutrition education, intervention, and recommendations can benefit from work on food-and cooking-related inspirations, influences and recipe selection motives with individuals, groups, communities, and populations [73]. The motives for food choice may also be a source of population level nutritional disparities both with lockdown and without lockdown.…”
Section: Conclusion Implications For Future Research and Practicementioning
confidence: 99%
“…Previous research has shown that due to the complexity of human food choices, the recommendation process can be manipulated through sophisticated nudging techniques such that a particular, 'healthier' recipe will be chosen more often than would be expected by chance alone [51]. Findings can be used to study the clustering of unhealthy dietary patterns and factors affecting diet-related disease, disease-disease interactions, and social condition interactions [73].…”
Section: Conclusion Implications For Future Research and Practicementioning
confidence: 99%
“…Motivations are probably one of the most frequently researched determinants among psychological factors. There are several instruments measuring eating motivations and related concepts [ 24 ], including the Eating Motivation Survey (TEMS) [ 25 ], the Eating Motivation Scale (EATMOT) [ 26 ], the Food Choice Motives Questionnaire [ 27 ], the Food Choice Questionnaire [ 28 ], and the Measure of Food Choice Values [ 29 ]. Some of the tools are focused on the specific context, e.g., ethical motivations (Measurement of Ethical Food Motives) [ 30 ], psychological motivations to eat or to abstain, including coping, social compliance, and pleasure motivations (The Motivations to Eat Measure) [ 31 ], hedonic eating behaviors (Palatable Eating Motives Scale) [ 32 ], orientation towards health and hedonic characteristics food on the market (Health and Taste Attitudes Scales) [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…EATMOT has been proposed as a tool that can be used for various objectives in diversified populations and geographical locations [ 24 ]. As it seems, multiple subpopulations and communities may differ significantly regarding the motivations playing a key role in food selection.…”
Section: Introductionmentioning
confidence: 99%